Study of physical and mechanical properties of plant fruits on the example of walnut - Pyatak, M.; Padalka, V. (Scientific Progress & Innovations, 2024)
Perennial plantations that are zoned in Ukraine allow to obtain high-quality fruits (nuts), which are widely used in the perfumery, pharmaceutical, oil, confectionery and other industries, as well as in the production of feed and feed additives. The known technologies of mass processing of walnut kernels mostly work well with crops that have a spherical or close to spherical external shape. The simplest, but least productive, are primitive manual devices for peeling walnut shells. Despite the simplicity of their design, these devices are inefficient and unsuitable for adjusting their operation to different varieties and physical and mechanical properties of biological fruits. The analysis of the known designs of walnut shell destruction machines and mechanisms showed the need to study the physical and mechanical properties of biological fruits (walnuts), to develop technical recommendations for the design of impact mechanisms to improve the quality of shell destruction and the possibility of their application in mass production technologies. A research methodology was developed, a laboratory setup was manufactured, and experiments were conducted. To determine the strength characteristics, the author designed and manufactured a device. It consists of a lever mechanism and a deforming device. The dimensions and load measurements were carried out according to well-known methods of physical mechanics. The statistical analysis of the results showed the need for in-depth scientific research of the geometric parameters of the design of the working bodies of machines for destroying the walnut shell in the mechanisms of fruit peeling machines, taking into account the quality indicators performance of works with certain conditions of their implementation. We conclude that according to the results of the experiments, there is a fairly high dependence between the geometric dimensions of the walnut fruit at the level of 0.72, 0.57 and 0.49, respectively. The weight of the fruit also depends on its dimensional characteristics, which is logical at the level of 0.6–0.75. The force of critical static fracture has a weak correlation with the dimensional characteristics at the level of 0.3. And it depends little on the plane of its application.